O3. Accurate Monte Carlo modelling of an Elekta Synergy equipped with an Agility 160-Leaf MLC. (September 2016) - Oderinde, O.; du Plessis, F.
Abstract : Introduction: The Agility TM multileaf collimator (Elekta AB, Stockholm, Sweden) is designed to meet present day demand for fast, accurate, and efficient radiation treatment. Agility's leaf speeds are twice as fast as previous MLCs produced. Specifically, Agility is utilized for advanced radiotherapy such as VMAT. The aim of this study was to characterize photon beams using a detailed linac model in BEAMnrc of the Linac equipped with an Agility MLC and to validate the beam data with measurements. Materials and Methods: The head of the Linac was simulated for 1 × 1 up to 30 × 30 cm 2 square field sizes for 10 MV photon beams using the BEAMnrc MC Code. Photon beam data were calculated in a homogenous water phantom using the DOSXYZnrc MC Code. The MC calculations were validated by water bath measurements that included beam profiles, depth dose and relative output factors. Results: For the square field sizes considered, the MC calculations and physical measurements agreed to within 2.1% for percentage depth doses (PDDs), lateral dose profiles and output factors. Conclusion: BEAMnrc input linac model is highly accurate up to 2%/2 mm. It has the potential to be used for dose calculation in advanced radiotherapy treatment planning.